KONTRIBUSI USAHA NIRA AREN YANG DIJADIKAN SOPI TERHADAP PENDAPATAN PETANI SOPI DI NEGERI HATUSUA KECAMATAN KAIRATU KABUPATEN SERAM BAGIAN BARAT - Solissa, Roberto; Imlabla, Wilma (PT. BARRINGTONIA ASIATICA LESTARI, 2024)
The aim of the research is to find out the contribution of sopi products to the level of income of sopi farmers and, to find out what factors influence the production and sales of sopi products in Hatusua State, West Kairatu Seram District. From the research results, the contribution of sopi is 66.84% or Rp. 561,497,810 per year. Meanwhile, income outside of beef production contributed 33.16% or Rp. 278,600,000 per year. From the results of the research and calculation of the contribution value to the income value of sopi production and income outside of sopi production. The income from sopi production in Hatusua Country has a very large contribution value, compared to the income contribution value outside of sopi production by sopi farmers. Factors that influence the production and sales of sopi in Hatusua State, Kairatu District, West Seram Regency, namely, factors that influence sopi production include weather, type of palm flower, age of palm trees and, type of mayang production level and, factors that influence sales. sopi is the status of a sopi which is still illegal.